A Fully‐Integrated Low‐Power Analog Front‐End for ZigBee Transmitter Applications. Issue 3 (1st May 2016) - Shi, Zuochen; Yang, Yintang; Li, Di; Liu, Yang
Abstract : A low‐power high‐linearity Analog frontend (AFE) composed by a Digital‐to‐analog converter (DAC) and a Low‐pass filter (LPF) is proposed in this paper for ZigBee transmitter applications. The DAC is realized by current‐steering topology which adopts an optimized segmentation method to resolve the contradiction between requirements of linearity and power. A Successive approximation register (SAR) frequency auto‐tuning operation is presented for the LPF to accommodate the performance deterioration due to the Process, voltage and temperature (PVT) variations. Implemented in a 0.13μm CMOS technology, the proposed AFE has been fully integrated in a ZigBee transceiver chip with an area of 1.23mm 2 . The experimental results demonstrate that it achieves a linearity of 30dBm Output 3rd order intercept point (OIP3) and dissipates 4.75mA from a 1.2V supply.